Study on Two Inoculation Routs of Salmonella enteritidis in Abilities to Colonize in Internal Organs and to Contaminate of Eggs in Broiler Breeder Hens - Maddadi, M.S.; Hassanzadeh, M.; Bozogmehrifard, M.; Shojaei, H.; Yazdani, A.; Karimi, V.; Barin, A. (International Journal of Poultry Science, 2010)
Two groups of chickens were inoculated orally and intravenously with 1010 and 106 CFU S. enteritidis organisms consequently. Heavier infection of liver spleen, caecum, small intestines, infundibulum-ovules and cloac-vagina of chickens that inoculated orally were observed. In intravenously inoculated group high infection of liver-spleen and cloac- vagina were noticed. In oral group egg production were more decreased and fecal shedding was higher than intravenously group.